تأكيد مفهوم الذات لدى عينة من مرضى السكر المراهقين من خلال الأنشطة الفنية - زيدان، هناء عبدالوهاب فريد (جامعة عين شمس - مركز الإرشاد النفسي, 2016)
يتناول البحث تقديم مجموعة من الأنشطة الفنية لتأكيد الذات لدى المراهقين من مرضي السكر مع تنظيم تعاطي الانسولين. \\ ترجع أهمية البحث إلى المشكلات النفسية التي يوجهها المراهقين المصابين بمرض السكر وعدم قدرتهم على التكييف مع الحالة المرضية واتخاذ التدابير والاحتياطات التي تجنبهم مخاطر ارتفاع أو انخفاض مفاجئ بمستوي السكر بالدم وعدم الرضي عن التعامل معهم طول الوقت على أنهم مرضي أو أصحاب إعاقة مما يسبب لهم الحرج بين أقرانهم ورفضهم لتوجيه النصح أو اتباع التعليمات اللازمة لسلامتهم، مما يسبب لهم الحرج من خلال تطبيق الأنشطة يقوم المراهق بنشاط مقنن إلى حد ما يمكن تقدير الجهد المبذول خلاله مع انتاج منتج فني تطبيقي أو شكل جمالي يقوم بخفض الشعور بالاكتئاب والضغط النفسي ويشعر المراهق بقيمة ما قام به من عمل ويزيده ثقة بنفسه وتأكيده لذاته. \\ قامت الباحثة بتطبيق مقياس توكيد الذات على المراهقين قبل وبعد تنفيذ مجموعة الأنشطة الفنية وبعد تحليل النتائج وتطبيق المعالجات الإحصائية المناسبة. \\ توصلت الدراسة الي ان أنشطة الفن التشكيلي والتي تساعد الفرد على التنفيس عما وبث الثقة في النفس لديه يمكن اتخاذها وسيلة عامة وللمراهق مريض السكر خاصة من خلال ممارسة الأنشطة الفنية الموجهة لتوكيد الذات للمراهق مع التنظيم المصاحب لتعاطي الانسولين.
This paper deals with providing a range of technical activities to diabetic adolescents to let them achieve self-assertion and regulate their insulin dosage. The importance of the research is owing to psychological problems faced by adolescents with diabetes and their inability to cope with the normal conditions and taking to account the measures and precautions to avoid the risk of high or low sudden sugar level in blood and their dissatisfaction to deal with them all the time as patients or as individuals with a disability which cause them embarrassment between their friends. As well as their refusal to the advice or to follow the instructions necessary for their safety. On the other hand, through the application of activities the teenager does a ruled activity that can be appreciated for his effort through the production of applied technical product or aesthetic form to reduce the feeling of depression, stress and the teenager feels the value of what he has done work and aggravated self-confidence and self-assertion. The researcher application of self-affirmation on adolescents scale before and after the implementation of technical activities group and after analyzing the results and applying appropriate statistical analysis processors. The study concluded that Fine art activities, which helps the individual to vent what inside and transmit the self-confidence he has, can be applied for this purpose generally, and for diabctic adolescents patients especially, ; through practice-oriented assertiveness concept by art activities accompanied by regulation of administration of insulin.
Keywords: الذات -- المراهقين -- مرضى السكر -- الأنشطة الفنية